The Antioxidant Test of Ecoenzymes from Various Fruit Peel Wastes - Napitupulu, Happy Chelsy Betaria; Pangela, Misael Ivan; Telaumbanua, Hepy Terima; Lase, Joy Sisokhi Putra; Tahya, Candra Yulius; Ringo, Sisilya Siringo (Indonesian Journal of Chemical Research, 2026)
Indonesia is a country with a large population and rapid industrial growth, facing serious challenges related to waste management. Waste is the remains produced by human activities. One interesting solution to handle the problem is the production of ecoenzymes through the fermentation process of natural organic waste materials. Ecoenzymes are biotechnology products that produce various types of enzymes and organic chemicals that are useful for various applications. Apart from that, laboratory tests also revealed the presence of antioxidant activity in these ecoenzymes, for Ecoenzyme A (IC50 = 13735.9 μg/mL) about 0.4 mL of ecoenzyme solution could inhibit 50% of radical activity, and for Ecoenzyme B (IC50 = 12029.4 μg/mL) about 0.3 mL solution could inhibit 50% of radical activity, and for Ecoenzyme C (IC50 = 15765.1 μg /mL) about 0.4 mL ecoenzyme could inhibit 50% of radical activity, which, although categorized as weak, is because the volume of ecoenzyme produced is very much greater (2 L) than the volume used for antioxidant testing, this product is much more economical and has enormous potential to be developed into cosmetic ingredients and other industrial products.